Streamlining Proses Bisnis Penyiapan Press Release Inflasi - Fitral Pratomo (Fakultas Teknik Universitas Hamzanwadi, 2021)
BPS-Statistics of Aceh Province routinely carries out inflation press releases. The process of preparing the press release requires a lot of time. Besides, the inflation data published in this press release was referred to by various parties such as researchers, agencies, and the mass media. Thus, the quality of the data presented must be maintained. This study is aimed at finding a more effective and efficient press release preparation process while maintaining the quality of the inflation data presented. The method used is the Business Process Improvement (BPI) regarding the 12 streamlining tools until the proposed business process is found. Furthermore, a simulation is carried out between the initial business processes and the proposed business processes that are found. This simulation proves that the proposed business process can significantly reduce press release preparation time by up to 74%. The number of business process activities decreases from 14 activities to 9 activities. On the other hand, choosing one of the streamlining tools, namely automation, is expected to be able to maintain the quality of the inflation data presented. Through this study, researchers also found that the BPI method was proven to be able to recommend a more effective and efficient business process for press release preparation